<span>A1 is the 1st term r is the difference, they can say "r" or "d" for the difference 1st a1 is the first term = -3 2nd "r" is the difference between each consecutive terms (coming after each other) = 1.5 the rule to get any term of the sequence as we add 1.5 each time is --> a1+(n-1)*d a1 --> 1st term , n --> order of the term u want whether 2nd, 3rd , 25th d --> difference so to get the 2nd--> -3+(2-1)*1.5= -1.5 to get the 3rd --> -3 +(3-1)*1.5 = 0 and so on</span>
Answer:
Part A
12 months a year means
%74.5 x 12 = $894
Part B
4 weeks in a month means
$74.5 ÷ 4 = $18.625
But rounded to the nearest penny. . .
$18.62
because in the thousandths place was a 5 and you round up when there is a 5 or above
Part C
We will go with 31 days in a month, but I will also do 30 for you
$74.5 ÷ 30 = $2.48333
But rounded to the nearest penny. . .
$2.48
because you round down when there is anything less than a 4
$74.5 ÷ 31 = $2.40322580645
But rounded to the nearest penny. . .
$2.40
because you round down when there is anything less than a 4
c constant of proportionality is 12
Step-by-step explanation:
36÷3= 12
The point that divides AB into a 3:2 ratio is calculated by (d) for a ratio of 3:2, divide AB into 5 equal parts. Each equal part is 2 units, so the point that divides AB into a 3:2 ratio is 2
<h3>How to determine the ratio?</h3>
The given parameters are:
A = -4
B = 6
Start by calculating the length AB using:
AB = |B - A|
This gives
AB = |6 -(-4)|
Evaluate
AB = 10
Next, the length is divided into 5 parts.
So, the length of each part is:
Length = 10/5
Length = 2
The point on the location 3 : 2 is then calculated as:
Point = A + 3 * Length
This gives
Point = -4 + 3 * 2
Evaluate
Point = 2
The above computation is represented by option (d)
Read more about number lines at:
brainly.com/question/4727909
#SPJ1
Step by step solution :<span>Step 1 :</span><span>Equation at the end of step 1 :</span><span><span> (((3•(x2))•(y4))3)
4•——————————————————
((2x3•(y5))4)
</span><span> Step 2 :</span></span><span>Equation at the end of step 2 :</span><span><span> ((3x2 • (y4))3)
4 • ———————————————
24x12y20
</span><span> Step 3 :</span><span> 33x6y12
Simplify ————————
24x12y20
</span></span>Dividing exponential expressions :
<span> 3.1 </span> <span> x6</span> divided by <span>x12 = x(6 - 12) = x(-6) = 1/<span>x6</span></span>
Dividing exponential expressions :
<span> 3.2 </span> <span> y12</span> divided by <span>y20 = y(12 - 20) = y(-8) = 1/<span>y8</span></span>
<span>Equation at the end of step 3 :</span><span> 27
4 • ——————
16x6y8
</span><span>Step 4 :</span>Final result :<span> 27
—————
4x6y<span>8</span></span>